2006
DOI: 10.3171/ped.2006.105.5.428
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of a cerebral arteriovenous malformation in a child with hereditary hemorrhagic telangiectasia

Abstract: Patients with hereditary hemorrhagic telangiectasia (HHT) are at risk for the development of cerebral arteriovenous malformations (AVMs). The authors report a case of a spontaneously regressing cerebral AVM in a patient with HHT. The lesion was diagnosed on the basis of findings on screening magnetic resonance imaging and regressed completely before any treatment was undertaken. The spontaneous regression of cerebral AVMs is a rare and poorly understood phenomenon. Only one other instance of spontaneous regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
2
13
0
1
Order By: Relevance
“…There are several case series and reports of catastrophic haemorrhagic sequelae of CVMs and spinal AVFs occurring during childhood 50 55–58. Rarely, spontaneous resolution of CVMs has been reported 59 60…”
Section: Cerebral Vascular Malformationsmentioning
confidence: 99%
“…There are several case series and reports of catastrophic haemorrhagic sequelae of CVMs and spinal AVFs occurring during childhood 50 55–58. Rarely, spontaneous resolution of CVMs has been reported 59 60…”
Section: Cerebral Vascular Malformationsmentioning
confidence: 99%
“…18,20 It has been suggested that HHT-2 may disproportionately involve smaller vessels in tissues with more significant vascular remodeling. 17 Reports of growth and spontaneous regression of cerebral AVMs [21][22][23] with endothelial proliferation on histology indicate that active angiogenesis may play a role in the growth and regression of AVMs in HHT. 24 Interestingly, anecdotal reports of antiangiogenic drugs such as bevacizumab, an antibody to vascular endothelial growth factor (VEGF), and interferon have been associated with improvement in nosebleeds and facial telangiectases, 25 a reduction in gastrointestinal bleeding 26,27 and amelioration of heart failure.…”
Section: Hereditary Hemorrhagic Telangiectasia (Hht)mentioning
confidence: 99%
“…First, the assessment of the risk associated with treatment might be complicated by presentation of multiple lesions. Secondly, given the more dynamic nature of these lesions provided by numerous reports on lesion growth or regression, [26][27][28] the determination of prognosis might be further complicated by frequently changing angiographic parameters. In addition, under most circumstances, the most compelling presenting symptoms were usually non-neurologic; therefore, the priority of treatment should be directed to other HHT-related lesions instead of intracranial AVMs.…”
Section: Management Strategymentioning
confidence: 99%